Satellite versus ground-based estimates of burned area: A comparison between MODIS based burned area and fire agency reports over North America in 2007. (August 2016) - Mangeon, Stéphane; Field, Robert; Fromm, Michael; McHugh, Charles; Voulgarakis, Apostolos
North American wildfire management teams routinely assess burned area on site during firefighting campaigns; meanwhile, satellite observations provide systematic and global burned-area data. Here we compare satellite and ground-based daily burned area for wildfire events for selected large fires across North America in 2007 on daily timescales. In a sample of 26 fires across North America, we found the Global Fire Emissions Database Version 4 (GFED4) estimated about 80% of the burned area logged in ground-based Incident Status Summary (ICS-209) over 8-day analysis windows. Linear regression analysis found a slope between GFED and ICS-209 of 0.67 (with R = 0.96). The agreement between these data sets was found to degrade at short timescales (from R = 0.81 for 4-day to R = 0.55 for 2-day). Furthermore, during large burning days (> 3000 ha) GFED4 typically estimates half of the burned area logged in the ICS-209 estimates.